THE INFLUENCE OF LOGISTIC ENGLISH PROFICIENCY TOWARDS WORKING ABILITY OF MARITIME UNIVERSITY ALUMNI - Rahayuningsih, Mahsunah Etik; Winarni, Endra (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
The long-term goal of this research is Logistic English which is needed by maritime students, especially the port management study program, due to they have to master it, especially ESP (English for Special Purpose) Logistics. In addition, many alumni work for foreign shipping companies. This inspires the writer to conduct this research. The study entitled